1999
DOI: 10.1002/(sici)1096-9071(199909)59:1<91::aid-jmv15>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytomegalovirus antigenemia and culture assays in patients on and off antiviral therapy

Abstract: We examined 1,869 consecutive blood specimens from 529 patients (>80% organ transplant recipients) for detection of CMV by antigenemia and culture assays, and compared results between patients on and off antiviral therapy. All 1,869 specimens were tested by the shell vial assay and antigenemia, and 503 were also tested by standard tube culture. The overall positivity rate for each test was 17.0% for antigenemia, 1.8% for shell vial culture assay, and 0.7% by tube culture. No specimens were positive by either s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…However, the association of CMV with TxCAD requires confirmation: although initial studies suggested the involvement of CMV in the pathogenesis of Tx-CAD (23,24), further investigations were unable to corroborate this association (19 -21). These discrepancies can probably be explained by the retrospective study design (23), the inadequacy of coronary angiography for TxCAD diagnosis (18), and by the insufficiently sensitive techniques used for CMV infection detection (25). Our prospective IVUS-based analysis focused on the occurrence of CMV infection as assessed by the pp65 antigenemia test (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association of CMV with TxCAD requires confirmation: although initial studies suggested the involvement of CMV in the pathogenesis of Tx-CAD (23,24), further investigations were unable to corroborate this association (19 -21). These discrepancies can probably be explained by the retrospective study design (23), the inadequacy of coronary angiography for TxCAD diagnosis (18), and by the insufficiently sensitive techniques used for CMV infection detection (25). Our prospective IVUS-based analysis focused on the occurrence of CMV infection as assessed by the pp65 antigenemia test (14).…”
Section: Discussionmentioning
confidence: 99%
“…Our prospective IVUS-based analysis focused on the occurrence of CMV infection as assessed by the pp65 antigenemia test (14). This assay expresses an accurate index of viral load in the blood and thus provides a highly sensitive tool to drive preemptive treatment (25,26). Furthermore, although previous IVUS-based studies examined TxCAD risk factors focusing only on intimal thickness (20,21), we analyzed coronary lumen behavior as the result of the interplay between both intimal hyperplasia and the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Cytomegalovirus is one of the most im- * portant infectious agents that attack transplant patients and is responsible for the significant morbidity and mortality presented by organ recipients (2,16). Since antigenemia started to be used as a quantitative marker of viral load, more extensive studies on the interaction between CMV and host immune response have become possible.…”
Section: Discussionmentioning
confidence: 99%
“…Cytomegalovirus (CMV) is one of the most important causes of infectious complications in organ transplant recipients (1,2). It occurs in 43-92% of kidney transplant recipients during the first months after transplantation and is associated with a greater net state of immunosuppression (3).…”
Section: Introductionmentioning
confidence: 99%